Vom Affen zum Übermenschen und zurück Theoretische, historische und literarische Ansätze über Evolution und Regression - Franchini, Stefano; Guerra, Gabriele; Ruster, Thomas (animate theologies, 2023)
If man is descended from the ape, what will become of man? No news could have hit the bourgeois of the 19th century worse than the news that they descended from the ape. Of all things from the ape! - this grotesque distorted image of the cultivated man, of whom in the colloquial language of that time was spoken merely in a derogatory, discriminating sense. Even the guardians of the world order, first and foremost the theologians, were shocked. Now what was the matter with the well-established ladder that reached from heaven to the underworld and assigned man a place next to God, far above the animals? Has the image of God become the image of the ape? The shock waves of the cultural commotion The theory of evolution hit the intellectual world like a meteorite. The concept of human being was deeply hit and wounded. How sapiens relate to the animal world and whether there is any difference at all had to be determined anew. Nietzsche resolutely drew the line beyond man and proclaimed the superior human. Kafka, Benn and Canetti went other, incomparable ways. The newfound photography, in that a mirror of its time, got the animals as objects in front of the lens and shot pictures like hunting shots. Creative theologians reassembled their doctrinal buildings. Anthroposophy swung to fantastic cosmologies. Meanwhile, the industrialization of animal exploitation progressed. The question of how humans relate to their animal relatives remains viral to this day. - Reactions to Darwin's theory of descent from a multidisciplinary perspective - A treasure trove for the human-animal debate - Future scenarios of the human-animal relationship - Cooperation of an Italian-German research group Between "Décréation" and Transhumanism The twelve contributions in this volume, which emerged from a conference in Rome, go beyond the historical search for traces to discuss the question of the future of the human-animal relationship. Would it be good if humanity abolished itself? Or can technical optimization help to get out of the "affinity" with animals? With that, the volume reaches the core question of contemporary political ecology.